Attitude Components Towards Online Purchase Intention - Wicaksono, Teguh; Syahrani; Shahrial Putra, Defin (International Journal of Science, Technology & Management, 2022)
As the behaviour main foundation, intention gives a strong contribution in leading behaviour to perform certain actions. It is necessary to prove empirically the psychological factor towards online purchase intention through attitude components, which are cognitive, affective, and conative. The aim of this study is to empirically describe and give evidence about the impacts of cognitive, affective, and conative levels on online purchase intention. The data is collected using survey and statistically analysed with multiple linear regression, engaging 150 respondents. The results of the study prove that cognitive and conative levels have a significant impact on online purchase intention, while the affective level does not give any impact towards it. The conative level is a factor that gives the greatest impact on online purchase intention, which means that the conveniences offered on online purchasing are the biggest aspects that lead to a desire to do online purchasing. The willingness to do online purchasing will result to a strong online purchase intention.